Revival of an old modern snake: taxonomic status of Dryophylax nattereri (Mikan 1820) (Serpentes, Dipsadidae, Tachymenini) - Trevine, Vivian C.; Gassner, Georg; Schweiger, Silke; Pinto, Roberta R.; Franco, Francisco L.; Zaher, Hussam (Zootaxa, 2026)
The genus Dryophylax currently comprises 15 widely distributed South American species of snakes. Despite recent efforts to clarify the systematic status of the genus, several species remain taxonomically poorly defined. One example is Dryophylax nattereri (Mikan 1820), regarded first as a junior synonym of Thamnodynastes strigilis (Thunberg 1787), and later as a junior synonym of Thamnodynastes pallidus (Linnaeus 1758). Despite several historical taxonomic studies addressing other congeners, D. nattereri has been often neglected, and no author has attempted to test species boundaries. Recently, several authors referred to this taxon as Dryophylax cf. nattereri, after it was resurrected without a proper taxonomic justification. Here, we demonstrate that D. nattereri is a valid species, based on morphological data gathered from a large series of individuals distributed throughout its known distribution. We designated a neotype for D. nattereri and provide a detailed description of the species diagnostic characters, with additional data on external morphological variation, skull osteology and hemipenial morphology.